Serving the Very Small Enterprise Segment by Microfinance Institutions in the Arab World - Khaled, Mohammed (International Finance Corporation, Washington, DC, 2016)
Increasing access to finance for Very Small, Small and Medium Enterprises (VSEs/SMEs) has become an important goal for many governments and development agencies as VSEs/SMEs are viewed as main drivers of economic growth and creators of employment. However, a missing middle between the ceiling of MFI lending and the segment defined by banks as SMEs is currently underserved and in some markets even unserved, despite the fact that it presents a significant growth opportunity for MFIs looking to upscale and/or to grow with their best clients. The report presents the findings of Sanabel’s and IFC’s VSE Survey which aimed to identify what has been done to date to serve the VSE segment, and how successful MFIs as well as other players in the region have been in catering to this segment and upscaling lending activities. This report represents the second report in a series of leadership papers, Voices, developed by Sanabel, the Microfinance Network of Arab Countries, and the International Finance Corporation (IFC).